2021
DOI: 10.1158/1078-0432.ccr-20-2667
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Comprehensive Genomic Landscapes of Pancreatic Ductal Adenocarcinoma Using Real-World Endoscopic Aspiration Samples

Abstract: Purpose: Most patients with pancreatic ductal adenocarcinoma (PDAC) present with surgically unresectable cancer. As a result, endoscopic ultrasound–guided fine-needle aspiration (EUS-FNA) is the most common biospecimen source available for diagnosis in treatment-naïve patients. Unfortunately, these limited samples are often not considered adequate for genomic analysis, precluding the opportunity for enrollment on precision medicine trials. Exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…[19][20][21] Furthermore, the suitability of PDAC FNA samples for comprehensive genomic analysis can be enhanced by applying an epithelial cell adhesion molecule-enrichment strategy. 18 RNA-based gene fusion analysis could not be performed in a significant number of biopsy cases, including 48% of FNA and 40% of FNB cases, because of insufficient or poor-quality RNA material, whereas the test was successful in all attempts in the resection specimens. Fortunately, gene fusions were rare molecular events in PDAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] Furthermore, the suitability of PDAC FNA samples for comprehensive genomic analysis can be enhanced by applying an epithelial cell adhesion molecule-enrichment strategy. 18 RNA-based gene fusion analysis could not be performed in a significant number of biopsy cases, including 48% of FNA and 40% of FNB cases, because of insufficient or poor-quality RNA material, whereas the test was successful in all attempts in the resection specimens. Fortunately, gene fusions were rare molecular events in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Not infrequently, FNA specimens are the only material available for additional studies. Some recent studies have suggested the feasibility of FNA material for comprehensive molecular testing 14‐18 . Furthermore, FNA material may serve as an optimal source for nucleic acids–based molecular analysis 19‐21 .…”
Section: Introductionmentioning
confidence: 99%
“…DNA was prepared as described previously 55 , including fragmentation with a Covaris LE 220 ultrasonicators system (Covaris) and library construction with the SureSelect XT HT–targeted enrichment protocol (Version A1, July 2017). Libraries were subsequently hybridized to a whole-exome capture library (SureSelect AllExonV7; Agilent, C/N: 5991-9039) and sequenced on a NextSeq500 (Illumina) using 300-cycle kits, paired-end.…”
Section: Methodsmentioning
confidence: 99%
“…These tumor subtypes represent a subset of 14% and 24% of all PDAC patients which may benefit from therapeutic regimens based on agents that induce DNA damage (i.e., iPARP). However, still, around 10% of these latter PDAC patients did not show response to platinum-based chemotherapy protocols in clinical trials, which may be due to (i) the lack of germline or somatic inactivating mutations in BRCA1/2 ("BRCAness" tumors) despite showing an HRD genomic profile [26], (ii) to common platinum resistance after secondary BRCA1 or BRCA2 mutations [126], (iii) upregulation of multidrug resistance transporters, and/or (iv) emerging EMT features in ATM-deficient neoplastic cells [127]. Altogether, these findings set the basis for the inclusion of genomic instability and the DSBR gene mutational profile genotypes in clinical trials (e.g., COMPASS [64]) based on platinum and/or novel drugs (e.g., iPARP) that target similar (DNA repair) mechanisms (Figure 2 and Supplementary Table S1).…”
Section: Therapeutic Implications Of Pdac Transcriptomics Profilesmentioning
confidence: 99%